O laicato na Conferência Episcopal Latino-Americana de Puebla - Scopinho, Sávio Carlos Desan (Revista eclesiástica brasileira, 2013)
This article studies the Ecclesiastical Magisterium understanding about the laity in the third Latin American Episcopal Conference held in Puebla (México), in 1979. Resuming the results of the Medellín Conference, the Puebla Conference proposed a definition of the laity from their mission and vocation in the Church and in the world. The proposal is to offer a diachronic and synchronic view, considering the Conclusive Document of the mentioned Conference as reference, with regard to the subject matter of the laity. So, the aim is to demonstrate that the layman, in the Latin American Ecclesiastical Magisterium conception, has had a historical and doctrinal progress, with challenges and deficiencies typical of their determined historical and social condition, verified in the preparation, accomplishment and deliberation steps of the Puebla Conference. The theological and pastoral interpretation of the Conclusive Document of the Conference will contribute to understand the development of the subject matter from the Latin American Episcopal Conferences of Rio de Janeiro (1955) and of Medellín (1969) to the Episcopal Conferences that were held later in Santo Domingo (1992) and in Aparecida (2007), regarding the role of the laity in the Church and in the society.